If this is life: rethinking the modern subject through the aporia of biopolitics - Aktokmakyan, Maral. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2016., 2016)
Drawing on the discussion of biopolitical modernity in the thoughts of Giorgio Agamben and Hannah Arendt, this thesis focuses on the biopoliticized life as manifested in the works of Zabel Esayan‘s Among the Ruins, Hagop Mntzuri‘s The Places Where I Have Been, William Faulkner‘s As I Lay Dying and Joseph Conrad‘s Heart of Darkness. While biopolitics, on a broader level, points to the disruption of the Aristotelian designation of the category of life as bios and zoe, it specifically comes to mean the management of lives by new power mechanisms in ways that deprive them of human agency. The main figures in all four works are examined primarily through their reduction to such a state of bodily existence or of objecthood. In the first two chapters, I deploy Agamben‘s discussion of Homo Sacer in order to present how Esayan and Mnzuri‘s works interrogate biopoliticized life as is the case with the Ottoman Armenians when their lives were radically stripped of a human quality. The next two chapters rework Arendt‘s notion of Animal Laborans in the stories of the Bundren family and of the pair Charles Marlow and Mr. Kurtz, and examine the glorification of labor, instead of action. The homo sacer and homo laborans figures in these works all embark on a journey which, in each specific case, fails to provide self-formation in the Hegelian sense. Their writing of their biopoliticized lives turns out to be an ―auto-bio-thanato-graphy,‖ out of which emerges a rather singular mode of subjecthood.
Keywords: Biopolitics.; Aporia.